Educational and Teaching Performance of Educators at the Faculty of Economics and Business, Manado State University (UNIMA): Analysis of Professional Competence and Motivation - Anas Romzy Hibrida; Tinneke Evie Meggy Sumual (AIBPM Publisher, 2022)
The quality of human resources in Indonesia is closely related to the quality of education, therefore higher education as one of the types of formal education plays an important role in realizing this. Education and teaching in universities during the Covid-19 Pandemic became a challenge in itself because there were various problems that affected the performance of educational personnel. The purpose of this study is to analyze the influence of professional competence and motivation on the educational and teaching performance of educators at the Faculty of Economics, Manado State University (FEB UNIMA) during the Covid-19 pandemic. This type of quantitative research takes data netted with a questionnaire of 40 educators who are willing to fill out the questionnaire. The results of this study show that there is a significant influence between the variables of professional ability and motivation on the educational and teaching performance of educators at FEB UNIMA during the pandemic. This study concludes that the improvement of research and teaching performance of educators is determined by professional ability and motivation. The results of this study recommend to educators to continue to improve professional abilities and work motivation so as to contribute more to improving their performance. Keywords: Professional Competence, Motivation, Educational and Teaching Performance, Educators, Covid 19 Pandemic